Predicting Moral Distress Through the Dimensions of Psychological Empowerment in Nurses - Mohammadi, Somayeh; Tajabadi, Ali; Roshanzadeh, Mostafa (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: Moral distress is an important challenge among critical care nurses. psychological empowerment can pave the ground for proper moral performance and prevention of moral distress among nurses. This study aimed to predicting moral distress through the dimensions of psychological empowerment in nurses. Methods: This descriptive cross-sectional and analytical study carried out in 2018. For this purpose, 190 nurses were selected by convenience sampling from the critical care units in Southern Khorasan Province, Iran. Data were collected using Corli's Moral Distress Questionnaire and Spreitzer's Psychological Empowerment Questionnaire. Data were analyzed in IBM SPSS ver. 16 using descriptive and inferential statistics. Results: Finding showed that moral distress intensity was (4.8±0.51) and negatively correlated whit psychological empowerment (P=0.03, r=-0.5). Moral distress frequency was (5.2± 0.56). The psychological empowerment was (4.1± 0.44). The results of the multiple regression indicated that 2 % variation of moral distress intensity explained by psychological empowerment (ADJ.R2:0.238). Among these dimensions, three dimensions meaning, competence and self-determination significantly predict the intensity of moral distress (R2=0.25, P< 0.05). Moral distress correlated with age, working experience, and type of the ward (P<0.05). Conclusions: Nurses with a greater psychological empowerment showed less intensified symptoms of distress where they were able to perform morally proper action.